The Effect of Epoxy Resin on the Compressive Strength of Short Laminated Bamboo Columns - Zulmahdi Darwis; Achmad Basuki; Muhammad Yani Bhayusukma; S A Kristiawan; Javil Egi Pratama Abdurahman; Muhammad Adha Ilhami (Logistic and Operation Management Research (LOMR), 2025)
The ongoing depletion of global timber resources has increasingly directed attention toward bamboo as a viable and sustainable structural alternative. This study investigated the influence of epoxy resin coatings on the compressive performance of short laminated bamboo columns. Three treatment conditions were evaluated: untreated (control), epoxy resin-coated, and externally reinforced with steel plates. The test specimens, manufactured using Dendrocalamus asper, were subjected to axial compression by SNI 03-3959:1995. Before testing, the physical and mechanical properties of both bamboo and steel reinforcement materials were characterized. Experimental results indicated that epoxy coating enhanced the average compressive strength by 2.54%, whereas steel plate reinforcement yielded a more substantial increase of 9.94% relative to the control group. One-way ANOVA analysis confirmed that only the steel-reinforced group demonstrated a statistically significant improvement in compressive capacity (p < 0.05). The observed failure modes revealed that the untreated and epoxy-coated specimens were prone to surface cracking and adhesive delamination, whereas the steel-reinforced columns exhibited a more localized damage with reduced deformation. It was concluded that although epoxy resin provided a modest enhancement, applying steel reinforcement significantly improved the axial load-bearing capacity of laminated bamboo columns. These findings underscore the structural potential of hybrid bamboo composites for sustainable construction applications.